Close-Proximity Operations Design, Analysis, and Validation for Non-Cooperative Targets with an Application to the ClearSpace-1 Mission - José Vasconcelos; Serena Gaggi; Tiago Amaral; Charles Bakouche; Adina Cotuna; Ana Friaças (Aerospace)
This paper addresses the design, analysis, and validation of safe close-proximity operations around uncooperative targets, with an application to the ClearSpace-1 (CS-1) mission. It is focused on the areas of Guidance, Navigation, and Control (GNC), and Mission Analysis, due to their criticality for the success and safety of this kind of operation. The relevance of the concepts, of the GNC solutions, and their validation is demonstrated for the case study of CS-1, a reference mission for the rendezvous, capture, and de-orbiting of an uncooperative target (i.e., the VESPA payload adapter). It is shown how the design approach can be adopted for the Concept of Operations of CS-1, covering the definition of keep-out zones, corridors, and GO/NO GO criteria, for assessing the passive safety of trajectories, and for the incorporation of active safety strategies. The analysis is adopted for functional chains such as the Navigation and Control, and the combination of a prototyping and a high-fidelity simulator is adopted for directed Model-in-the-Loop Monte-Carlo campaigns. The outcomes are intended to support the industry in the development of Close-Proximity Operations similar to that of CS-1. These can be adopted in a wide variety of missions, including Active Debris Removal and In-Orbit Servicing. In particular, the adopted concepts are a key contribution to the standardization of Close-Proximity Operations for non-cooperative rendezvous missions, and act towards a sustainable and safe commercial application.